2016
DOI: 10.1002/jbt.21868
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation promotes CCL27 secretion from keratinocytes through the cross talk between TNF‐α and ROS

Abstract: The skin-associated chemokine CCL27 and its receptor CCR10 mediate the immune response of skin-homing T cells. The CCL27 secreted from keratinocytes was reportedly involved in inflammatory skin diseases such as atopic dermatitis, contact dermatitis, and psoriasis. However, whether ionizing radiation increases the levels of CCL27 secretion still remains unclear. In HaCaT cells, a human keratinocyte cell line, CCL27 secretion was markedly increased after X-ray irradiation. We further found that irradiation boost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Our study found a positive correlation between serum levels of CCL27 and TNF-α during the acute stage. Several studies have shown that TNF-α can induce keratinocytes to secrete CCL27 in vitro [ 13 , 32 ]. Taking these findings into account, we hypothesized that the keratinocytes amplify inflammation in SJS/TEN.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found a positive correlation between serum levels of CCL27 and TNF-α during the acute stage. Several studies have shown that TNF-α can induce keratinocytes to secrete CCL27 in vitro [ 13 , 32 ]. Taking these findings into account, we hypothesized that the keratinocytes amplify inflammation in SJS/TEN.…”
Section: Discussionmentioning
confidence: 99%
“…RONS levels increase at multiple time points in vitro and in vivo following IR indicating a persistent effect (Fig. 2) (Ameziane- El-Hassani et al 2015;Choi et al 2007;Das et al 2014;Datta et al 2012b;Denissova et al 2012;Du et al 2009;Lyng et al 2001;Manna et al 2015;Martin et al 2014;Narayanan et al 1997;Pazhanisamy et al 2011;Saenko et al 2013;Werner et al 2014;Yang et al 2005;Yoshida et al 2012;Zhang et al 2017). Ionizing radiation initially generates RONS by direct hydrolysis of water molecules.…”
Section: Evidence Of Activation By Irmentioning
confidence: 99%
“…Similarly, decreased antioxidant activity and higher RONS are observed in cells with GI (Bensimon et al 2016;Buonanno et al 2011;Datta et al 2012b;Dayal et al 2008;Kim et al 2006;Natarajan et al 2007;Owens et al 2012;Pazhanisamy et al 2011;Thomas et al 2012). RONS are also involved in the activation of inflammation (Nakao et al 2008;Zhang et al 2017) and epigenetic effects (Bernal et al 2013;Galligan et al 2014;Kloypan et al 2015;Simone et al 2009;Yang et al 2014).…”
Section: Essentiality Of Ronsmentioning
confidence: 99%
See 2 more Smart Citations